Review of the genus Qinshuiacris (Orthoptera: Acrididae) from China with proposal of Caryanda viridis-species group and description of a new species - Mao, Ben-Yong; Niu, Yao; Zheng, Zhe-Min; Scott, Matthew B. (Zootaxa, 2015)
Based on an examination of type and additional material, Qinshuiacris viridis Zheng & Mao, 1996 and some allied species in the genus Caryanda are reviewed. Q. viridis Zheng & Mao, 1996 is transferred to Caryanda as a new combination: C. viridis (Zheng & Mao, 1996) comb. nov.. The female of C. viridis is described for the first time and sixty-two topotypes are designated. The genus Qinshuiacris Zheng & Mao, 1996 is synonymized with Caryanda Stål, 1878 because of the transfer of the type species. C. yini Mao & Ren, 2006 is proposed as a new junior synonym of C. dehongensis Mao, Xu & Yang, 2003. A new species, C. eshana Mao sp. nov., is also described and illustrated. Additionally, the conception of the Caryanda viridis-species group is proposed to contain the four allied species with falciform cerci: C. albomaculata Mao, Ren & Ou, 2007, C. dehongensis Mao, Xu & Yang, 2003, C. eshana Mao sp. nov., and C. viridis (Zheng & Mao, 1996) comb. nov.. A key to the species of C. viridis-species group is provided. Type specimens are deposited in the Biological Science Museum, Dali University (BMDU), Yunnan Province, China, in the Institute of Zoology, Shaanxi Normal University (IZSNU), Shaanxi Province, China and in the Institute of Zoology, Chinese Academy of Sciences, Beijing, China (IZCAS).